Pengembangan Kamus E-Mnemonic Sebagai Sumber Belajar Siswa Sejarah SMA - Anik Dwika Lestari; Ofianto Ofianto (Jurusan Sejarah FIS UNP, 2023)
The skills to think historical research capabilities (skills to build historical significance) are the first skills that must be possessed by students, thinking historical research capabilities (skills to build historical significance) are generally a number of steps or scientific processes in history. one way to improve students' skills in building historical significance is by using interactive media packaged in a mnemonic dictionary, therefore this study aims to, 1. to find out whether the use of an e-mnemonic dictionary can improve students' historical significance skills. 2. The practicality of the e-mnemonic dictionary learning resources as a whole is in the practical category. 3. Knowing the effectiveness of e-mnemonic dictionary learning resources in improving skills in building historical significance. The research method is Research and Development (R&D), using the Thiagarajan 4D development model which consists of 3 stages of development namely definition, planning (design), and development (development). The results of the study show that, in general, the feasibility of e-mnemonic learning resources is feasible and able to help improve skills in building historical significance. keywords: interactive learning resources, e-mnemonic dictionaries, historical significance building skills, historical research capabilities. ABSTRAK Keterampilan berfikir historical research capabilities (keterampilan membagun arti penting sejarah) merupakan keterampilan pertama yang harus di miliki oleh peserta didik, berfikir historical research capabilities (keterampilan membangun arti penting sejarah) pada umumnya merupakan sejumlah langkah atau proses ilmiah dalam sejarah. salah satu cara dalam meningkatkan keterampilan siswa dalam membangun arti penting sejarah dengan menggunakan media yang interaktif yang di kemas didalam kamus mnemonic, oleh karena itu penelitian ini bertujuan untuk, 1.mengetahui apakah penggunaan kamus E-Mnemonic bisa meningkatkan siswa dalam keterampilan arti penting sejarah. 2. kepraktisan sumber belajar kamus e-mnemonic secara keseluruhan berada dalam kategori praktis. 3.mengetahui keefektifan sumber belajar kamus e-mnemonic dalam meningkatkan keterampilan membangun arti penting sejarah. Metode penelitian ini adalah Research and Development (R&D), menggunakan model pengembangan Thiagarajan 4D yang terdiri dari 3 tahap pengembangan yaitu pendefinisian, perencanaan (design), dan pengembangan (develop). dari hasil penelitian menunjukkan bahwa, kelayakan sumber belajar e-mnemonic secara umum menunjukkan layak dan mampu untuk membantu meningkatkan keterampilan membangun arti penting sejarah. keywords: sumber belajar interaktif, kamus e-mnemonic, keterampilan membangun arti penting sejarah, historical research capabilities.